Analysis of Inventory Management At The Regional Office of The National Land Agency of North Sulawesi Province - SENDUK, Adalee; GAMALIEL, Hendrik; KOROMPIS, Claudia Wanda Melati (Journal of Governance, Taxation and Auditing, 2022)
Inventory is a current asset that is used to support operational activities.. Inventory must be managed properly and carefully so that there are no mistakes that will create losses. To create good inventory management, accounting policies implemented by government agencies must be based on a strong guideline or standard. For inventory management, it is regulated in Statement of Government Accounting Standards Number 5 which includes the process of recognizing, measuring, recording, and disclosing inventory .The researcher took the object of research at the Regional Office of the North Sulawesi BPN because according to the initial survey, it was found that there were problems in recording inventory. This study aims to determine the inventory management in the Regional Office and what causes errors in inventory recording. The method used in this research is a qualitative method with a case study approach. The results showed that the inventory management at the North Sulawesi BPN Regional Office was carried out properly in accordance with Statement of Government Accounting Standards Number 5, problems that occur are caused by inventory items that have been recorded when taking goods from the warehouse and then at the time of hospitalization, the goods have not been used. However, the North Sulawesi BPN Regional Office still records the ending inventory balance according to the amount of usage.